Endoscopic Sphenopalatine Artery Cauterization in Recurrent Posterior Epistaxis: An Experience at Dhulikhel Hospital, Kathmandu University Hospital - Shrestha, BL (Kathmandu University Medical Journal, 2015)
Kathmandu University Medical Journal Vol.12(1) 2014: 85-86